2021
DOI: 10.1016/j.jshs.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between step count and all-cause mortality and cardiovascular events: A dose–response meta-analysis

Abstract: Highlights Higher step count is inversely associated with the risk of premature death and cardiovascular events. As measured by accelerometers, 8959 steps/day (Q3) had a 40.36% lower risk of all-cause mortality than 4183 steps/day (Q1). As measured by accelerometers, 9500 steps/day (Q3) had a 35.05% lower risk of cardiovascular events than 3500 steps/day(Q1). These associations were in nonlinear dose–response patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
1
47
2
Order By: Relevance
“…Our key findings suggest the shape of the dose‐response curve for most risk markers was L‐shaped, with linear associations up to around 10 000 steps a day. This is in contrast to previous studies on premature mortality that largely demonstrated optimal benefit at 7500 steps a day, 2 albeit for CVD events there continued to be some positive benefits beyond this cut‐point 6 …”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Our key findings suggest the shape of the dose‐response curve for most risk markers was L‐shaped, with linear associations up to around 10 000 steps a day. This is in contrast to previous studies on premature mortality that largely demonstrated optimal benefit at 7500 steps a day, 2 albeit for CVD events there continued to be some positive benefits beyond this cut‐point 6 …”
Section: Discussioncontrasting
confidence: 95%
“…However, daily step count has been used as a popular approach to provide relatively simpler physical activity targets for the general public. There has been limited research to empirically examine the shape of the dose‐response curve between step count and health outcomes which may contribute to the absence of formal recommendations on daily number of steps 2–6 . A recent meta‐analysis of 10 cohort studies showed that the association between step count and mortality was L‐shaped, with 8.5% mean risk reduction every 1000 steps/day up to around 7500 steps/day 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Panels formed by experts convened by national and international organizations—as well as the 1996 U.S. surgeon General’s report on physical activity and health—have reinforced the scientific evidence that physical activity positively affects various aspects of cardiovascular health [ 19 ]. Due to more than half a century of epidemiological studies, it is now generally undisputed that physically active people present lower risks for developing coronary heart disease compared to those who are inactive, and that physical activity patterns and cardiorespiratory fitness levels are associated with greater health outcomes [ 20 , 21 , 22 ].…”
mentioning
confidence: 99%